Hubungan Spiritual Well-Being dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 di Puskesmas Petungkriyono Kabupaten Pekalongan - Dirgantara Dwi Saputra; Menik Kustriyani; Rahayu Winarti P; Rahayu Winarti (Journal of Medical Practice and Research, 2026)
Type 2 diabetes mellitus represents a chronic metabolic disorder that may affect patients’ physical, psychological, and social well-being, thereby influencing their overall quality of life. Spiritual well-being has been recognized as an important psychosocial resource that may support coping and adaptation among individuals living with chronic illness. This study aimed to examine the relationship between spiritual well-being and quality of life among patients with type 2 diabetes mellitus receiving primary healthcare services at Puskesmas Petungkriyono, Pekalongan Regency. A quantitative cross-sectional design was employed involving 41 respondents selected through consecutive sampling. Data were collected using the Spiritual Well-Being Scale (SWBS) and the Diabetes Quality of Life (DQOL) instrument. Statistical analysis was conducted using the Spearman rank correlation test with a significance level of p < 0.05. The findings indicated that most participants demonstrated high levels of spiritual well-being and good quality of life. Statistical analysis revealed a significant positive correlation between spiritual well-being and quality of life (p = 0.006; r = 0.423). These results highlight the importance of incorporating spiritual dimensions within holistic healthcare approaches to enhance psychosocial adaptation and well-being among individuals living with type 2 diabetes mellitus.